Perioperative management of patients undergoing antithrombotic treatment in oral surgery in France: a survey - Touny Marion; Catros Sylvain; Fricain Jean-Christophe; Fénelon Mathilde (EDP Sciences, 2019)
Introduction: The prevention and treatment of thromboembolic events is generally based on the prescription of antithrombotics. These drugs are associated with an increased hemorrhagic risk. The procedures for the management of patients under antithrombotic treatment are described in the recommendations of the Société Française de Chirurgie Orale (SFCO), published in 2015. The main objective of this study was to describe dentists' knowledge and practices regarding the perioperative management of patients under antithrombotic agents in oral surgery in France. Materials and methods: A national cross-sectional study was conducted between June and September 2018. An electronic questionnaire was created on Google Forms and sent through social networks. Results: In total, 185 responses were collected. Two-thirds of the respondents reported that they were aware of the 2015 recommendations. Ten respondents reported that they did not manage patients treated with antithrombotic drugs. Among the respondents who managed such patients, 25% and 16% ordered hemostasis tests for patients treated with direct anticoagulants and antiplatelet agents, respectively. Discussion: Although 71% of dentists considered themselves properly informed, one-third stated that they were not aware of SFCO's 2015 recommendations. Among those who were aware of these recommendations, 47% correctly ordered hemostasis tests before surgery in patients on antithrombotic medication. Conclusion: This study indicates that there is a lack of knowledge and noncompliance with the recommendations among at least half the sample population regarding perioperative management of patients on antithrombotic therapy.